Apparent Herbivory and Indigenous Pathogens of Invasive Flowering Rush (Butomus umbellatus L.) in the Pacific Northwest - Harms, Nathan E; Shearer, Judy F (2015)
Butomus umbellatus L. (Butomaceae; flowering rush) is an invasive aquatic monocot of Eurasian origin, first observed in North America in the Saint Lawrence River in the late 1800s. The earliest U.S. populations were reported from River Rouge, MI in 1918 (Anderson et al. 1974) and subsequently throughout the Great Lakes region (Witmer 1964). Infestations now persist across the northern tier of the U.S., although evidence for multiple introductions from separate source areas exists. Plants in the Northwestern U.S. are mostly triploid, whereas populations in the northeast are more commonly diploid (Lui et al. 2005). Diploid plants are generally quite fertile and abundant seed-producers, while triploid plants are usually sterile (Lui et al. 2005). As such, the relative importance of sexual (seed) or vegetative (bulbils) propagation to spread flowering rush differs between geographic locations. Few studies have addressed ecosystem impacts associated with flowering rush. Limited data describing economic impacts indicate that dense, monotypic growth negatively affects water delivery in irrigation systems, decreases recreational use of waterbodies (through propeller-fouling and infesting swimming areas) (Boutwell 1990; Rice and Dupuis 2009) and may increase the occurrence of swimmer s itch (cercarial dermatitis) by increasing suitable habitat for pond snails, intermediate host organisms for the swimmer s itch parasite (Parkinson et al. 2010). Additional impacts include competition with native plant species for space and nutrients and colonization of previously unvegetated habitats, which support native fish species (e.g., cutthroat and bulltrout) (Parkinson et al. 2010; Jacobs et al. 2011). The value of flowering rush to wildlife is questionable, though its use as a waterfowl food has been documented (Martin and Uhler 1939).